The Role of Technology in Improving Language Skills (English and Arabic) among Early Childhood Children - Yuning Eka Rahma Wati; Dian Aggraini; Kholida Nur; Yeasy Agustina Sari (Bulletin of Pedagogical Research, 2024)
This research explores the role of technology in improving English and Arabic language skills among young children. In the current digital era, technology has become an important tool in the language learning process, especially for children. Through the use of interactive learning apps, educational videos and digital language games, children can more easily understand and practice both languages ​​in a fun and engaging way. In addition, technology also provides children with the opportunity to interact with native language speakers, thereby helping to improve their speaking and listening skills. This research also highlights challenges in implementing technology, such as limited access and parental supervision, as well as the importance of choosing content that is appropriate to children's ages and abilities. This research uses a qualitative approach with a case study approach. The research subjects were Khodijah Metro Metro Kindergarten students. The sampling technique for this research was carried out using a purposive sampling method which was carried out by selecting a number of respondents according to the research objectives. In this research, the individuals who will be used as informants are TK A students and teachers at Khodijah Metro Metro Kindergarten.